2010
DOI: 10.5251/abjna.2010.1.5.841.844
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type and levels of animal protein supplements on the growth rate of rats

Abstract: The experiment was designed to examine the effect of types and levels of animal protein supplements on feed intake, weight gain, feed conversion ratio and feed digestibility in rats. Thirty (30) weaning albino rats of the Wister strain were subjected to five dietary treatments, diet 1 (control diet) contained soybean meal only as a source of protein concentrate, diets 2 and 3 were supplemented with 2.5% and 5.0% levels of fish meal (FM) respectively while diets 4 and 5 were supplemented with blood meal (BM) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…The superiority of the Chinchilla in litter weight (at birth and weaning) is consistent with the findings of Obike and Ibe (2010).Variation in litter weight at birth due to breed-type effect as indicated by our result is in agreement with the findings of Hassanien and Balomy (2011) who obtained significant breed effect in medium size rabbits (Rex, California, New Zealand white, and Baladired). Lower litter birth weight in the New Zealand breed is also supported by the results of Addass (2010). Chineke (2005) found no breed effect on litter weight at birth between New Zealand white and Chinchilla breeds, et al et al et al, et al et al, et al, et al, et al, et al whereas Iyeghe-Erakpotobor (2001) in contrast, reported higher litter birth weight for New Zealand white rabbits than Chinchilla breeds.…”
Section: Traits Measured Statistical Analysismentioning
confidence: 80%
“…The superiority of the Chinchilla in litter weight (at birth and weaning) is consistent with the findings of Obike and Ibe (2010).Variation in litter weight at birth due to breed-type effect as indicated by our result is in agreement with the findings of Hassanien and Balomy (2011) who obtained significant breed effect in medium size rabbits (Rex, California, New Zealand white, and Baladired). Lower litter birth weight in the New Zealand breed is also supported by the results of Addass (2010). Chineke (2005) found no breed effect on litter weight at birth between New Zealand white and Chinchilla breeds, et al et al et al, et al et al, et al, et al, et al, et al whereas Iyeghe-Erakpotobor (2001) in contrast, reported higher litter birth weight for New Zealand white rabbits than Chinchilla breeds.…”
Section: Traits Measured Statistical Analysismentioning
confidence: 80%
“…Positive control feed was prepared by incorporating casein (1.5%) into the standard diet, and the negative control was given a regular diet without any alterations. 17 The standard feed was powdered to maintain consistency, and the required ingredients were added, pelletized, and dried to attain a consistent shape and size ( Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The rats were allowed to acclimatize for a period of one week before commencement of feeding with the experimental diets and the trials was carried out within duration of 28 days. Data were collected to determine the feed intake, body weight changes, feed conversion ratio (FCR) and protein efficiency ratio (PER) using the method of Addass et al [41]. Determination of hematological parameters (RBC, WBC and PCV) was carried out using the method of Bull et al [42].…”
Section: Animal Experimentsmentioning
confidence: 99%